THE CORRELATION BETWEEN STUDENTS' LANGUAGE LEARNING STRATEGY AND READING COMPREHENSION - Putri Wulandari; Fitri Novia; Kiki Rizki Amelia (Universitas Tridinanti Palembang, 2021)
The objective of the study was to find out whether or not there was a significant correlation between the eighth-grade students' language learning strategy and their reading comprehension at SMPN 3 Kayuagung. The population of the study was all the eighth-grade students of SMPN 3 Kayuagung. The total number of the populations was 189 students. The sample of the study was 100 students taken by using purposive sampling. To conduct this study, correlation research design was used. To collect the data, the questionnaire and reading test were used. Before giving the test to the samples, the test was tried out to non-sample students at SMPN 3 Kayuagung in order to know whether or not test was reliable and valid for samples or not. In order to analyze the data, the correlation analysis applied was Pearson Product Moment. Based on the result, it was found that the Correlation Coefficient or r-obtained (0.075), it was lower than r-table (0.195), at p-value: 0.461>0.05. The finding showed that there was no significant correlation between students' language learning strategy and their reading comprehension. The students did not apply language learning strategy in reading comprehension so that they got trouble in understanding a reading passage. Keywords: language learning strategy, reading comprehension